Possibilities for active tourist holidays in rural areas in the region of AP Vojvodina, Serbia - Vukovic, Predrag; Andrei, Jean Vasile; Kljajic, Natasa; Arsic, Slavica (Journal of Tourism Management Research, 2024)
The subject of the article is to research the possibility of active rural holidays in region of AP Vojvodina (Autonomous Province), with the goal of determining how it can improve tourist competitiveness. The aim is based on the outcome of practical research conducted on the attitudes of tourists and potential tourists about the quality of the supply and the possibilities for active holidays; to identify the elements of tourist supply chain that can have an influence on the active and potential future supply of rural destinations and propose strategic directions for improving their competitiveness. The obtained results of survey provided the opportunity to identify elements in tourist supply chain that are strongest and weakest; analyze current problems pointed out, and suggest strategic ways for further growth of rural tourism. They also suggested the ways to it the competitiveness of rural destinations. AP Vojvodina was selected as the target area for the following reasons: a high level of rural tourism development; the presence of numerous attractive factors that can favor active tourism holidays; high level of economic and social development; and a high level of local population awareness regarding the importance that rural tourism can have for the rise of local economy.